Linearization of Lipschitz-polynomial and Lipschitz-analytic mappings - Dubei, M.V.; Zagorodnyuk, A.V. (Carpathian Mathematical Publications, 2011)
We introduce and study Lipschitz-analytic and Lipcshitz-polynomial functions, analogues of tensor and symmetric tensor products of metric spaces. Using the analogues of tensor products of metric spaces and linearizations of analytic functions we construct a global linearization of Lipschitz-polynomial and Lipschitz-analytic maps.